Resilience and path dependency: Income distribution effects of GDP in Colombia - Ahmet Faruk Aysan; Dilek Demirbas; Mustafa Disli; Monica Shirley Chaparro Parra (Journal of Central Banking Theory and Practice, 2023)
This study examines the effect of GDP per capita on the Gini index, which measures income concentration, in Colombia. The methodology used is an econometric analysis of time series with data extracted from the Inter-American Development Bank and the World Bank. The econometric results suggest that, at least during the period studied here, there is no evidence that GDP per capita has been an explanatory variable of the behaviour of income distribution in Colombia. The results also align with the understanding that the problem of inequality in the distribution of income is not merely economic but concerns persistent matters such as political and historical issues.
Keywords: C43; D6; H3; H11; H21; 330; Income Distribution; Colombia; Resilience; inequality